From Darkness to Brightness: An Analysis of PTSD in Abrahamson’s Room, Using Emotional Processing Theory - Lai, Yan-Ping; Wang, Ya-huei (LINGUISTICA, 2025)
The aim of this study was to use Abrahamson’s film Room as a case study to examine how PTSD may influence people’s lives and how they can use emotional processing to turn their extreme feelings into something positive. In order to reach this objective, Foa and Kozak’s emotional processing theory was used to analyze the protagonist,Joy “Ma” Newsome, with respect to various traumatic situations and resulting PTSD symptoms she has experienced, as well as her attempts to use emotional processing to cope with her psychological disorder and find meaning in the traumatic events in order to live again. The ultimate goal of this study was to help readers confront their own traumatic memory; although the world is not as perfect as we think, we can use Foa and Kozak’s emotional processing theory as a mechanism to make sense of traumatic experiences and bring about a positivechange.Keywords: emotional processing theory; mental disorder; PTSD; traumamemory.